2002
DOI: 10.1177/074193250202300106
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Perceptions of the Trustworthiness, Usability, and Accessibility of Information From Different Sources

Abstract: This study examined practicing teachers' assessments of the trustworthiness, usability, and accessibility of intervention information obtained from four sources: other teachers or colleagues, workshops and inservice presentations, college courses, and pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 12 publications
3
52
1
1
Order By: Relevance
“…Interestingly, empirical evidence was rated higher than teacher advice in the current study yet Landrum et al (2002) reported that late-stage trainee teachers viewed advice as more accessible, usable and trustworthy than professional journals. This apparent discrepancy might be accounted for by the exclusive focus of Landrum et al (2002) on the source of the information (i.e., professional journals), rather than the nature of the content (empirical research).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Interestingly, empirical evidence was rated higher than teacher advice in the current study yet Landrum et al (2002) reported that late-stage trainee teachers viewed advice as more accessible, usable and trustworthy than professional journals. This apparent discrepancy might be accounted for by the exclusive focus of Landrum et al (2002) on the source of the information (i.e., professional journals), rather than the nature of the content (empirical research).…”
Section: Resultsmentioning
confidence: 68%
“…This apparent discrepancy might be accounted for by the exclusive focus of Landrum et al (2002) on the source of the information (i.e., professional journals), rather than the nature of the content (empirical research). It was also of note that empirical research was specifically rated higher than research in general in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, much of this reading involved practically orientated periodicals as compared to research-based professional journals. Landrum, Cook, Tankersley, and Fitzgerald (2002) reported that both regular and special education teachers rate the opinions of colleagues, workshops and in-service programs as not only more accessible and usable, but more trustworthy than professional journals. Further, Boardman, Arguelles, Vaughn, Hughes, and Klinger (2005) reported that when making decisions about classroom implementation of practices, special education teachers did not consider it important that they be research-based.…”
Section: How Do Teachers Know What To Do In the Classroom?mentioning
confidence: 97%
“…This lack of relationship between researchers and practitioners is expanded upon by Landrum, Cook, Tankersley and Fitzgerald (2002), who point out that, "teachers rated professional journals and college coursework as generally less trustworthy than their own colleagues" (p. 46). This tendency to consult colleagues is certainly noted in the literature surrounding research utilization.…”
Section: Teachers' Attitudes Towards Published Research -What Does Thmentioning
confidence: 99%